Characterizing nanoscale coherent double-solid-solution interfaces between non-reactive Mg and steel alloys - Qiang Lang; Taotao Li; Muhammad Shehryar Khan; Gang Song; Liming Liu (Materials & Design)
Achieving coherent interface matching between immiscible Mg and Fe alloys is a significant challenge due to significant differences in their lattice constants and structures. Although the introduction of a third element into the interfacial metallurgical reaction has been explored before, it has been difficult to avoid the formation of brittle intermetallic compounds with poor mechanical properties. This study presents a groundbreaking method that, for the first time in published literature, leverages in-situ Ni alloying with a flexible laser-arc hybrid heat source to create an exceptionally high-performing nanoscale double solid solution interface between immiscible Mg and Fe alloys. This processing approach enables the high metallurgical reaction temperatures required for immiscible and nonreactive systems. The resulting lattice formation, driven by localized elemental diffusion at elevated interfacial temperatures, fosters adaptive coherent matching across the entire Mg-Fe interface. This process successfully transforms the non-coherent lattice that is generally observed at the Mg/Fe interface into a coherent double solid solution interface with the bulk matrix on both sides, significantly enhancing bonding efficiency and performance. This study provides detailed advanced characterization of the nanoscale double solid solution structures observed at the interfaces of these immiscible dissimilar metals which has been previously unexplored in the literature.